Evaluasi Penanganan dan Identifikasi Bakteri Penyebab Abses Subkutan Hipodermis Pada Anjing di Klinik ZZ Petcare Mataram - Gusti Ayu Esty Windhari; Fitrah Ramdani; Alifianita Anake Yansri; Balqis Ria Putri (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aimed to analyze the management of a subcutaneous abscess in a Shih Tzu dog, including identification of the causative agent, antibiotic sensitivity testing, and evaluation of the clinical therapeutic response. The case was managed at ZZ Petcare Clinic using a systematic approach consisting of anamnesis, physical examination, ultrasonography (USG), aseptic collection of pus samples, local drainage, abscess cavity irrigation, and follow-up treatment with broad-spectrum antibiotics, amoxicillin, vitamin B complex, and topical antibiotics. Pus samples were analyzed in the laboratory for bacterial isolation and identification using biochemical tests, while hematological examination was performed to assess the patient’s systemic status. Ultrasonographic examination identified an accumulation of purulent fluid with an approximate diameter of 7 cm, accompanied by an inflammatory response in the subcutaneous tissue. Laboratory analysis of the pus revealed that the causative agent of the abscess was Staphylococcus aureus, with antibiotic susceptibility testing showing sensitivity to ciprofloxacin, intermediate susceptibility to amoxicillin, and resistance to penicillin and ceftriaxone. Initial hematological examination indicated leukocytosis and mild inflammatory anemia, with WBC and RBC values of 20.4 × 10⁹/L and 5.05 × 10⁹/L, respectively. Following therapy, the patient’s condition improved, as evidenced by normalization of white blood cell and red blood cell parameters, with WBC and RBC values of 7.8 × 10⁹/L and 7.96 × 10⁹/L, respectively. The therapy administered was sufficiently effective, as indicated by clinical improvement within five days after treatment. This study emphasizes the importance of combining local drainage procedures, appropriate wound care, and antibiotic selection based on susceptibility testing in controlling infection and promoting patient recovery.